2002
DOI: 10.1074/jbc.m200971200
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated Fatty Acyl Coenzyme A Suppress the Glucose-6-phosphatase Promoter Activity by Modulating the DNA Binding of Hepatocyte Nuclear Factor 4α

Abstract: Glucose-6-phosphatase confers on gluconeogenic tissues the capacity to release endogenous glucose in blood. The expression of its gene is modulated by nutritional mechanisms dependent on dietary fatty acids, with specific inhibitory effects of polyunsaturated fatty acids (PUFA). The presence of consensus binding sites of hepatocyte nuclear factor 4 (HNF4) in the ؊1640/؉60 bp region of the rat glucose-6-phosphatase gene has led us to consider the hypothesis that HNF4␣ could be involved in the regulation of gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 50 publications
3
79
0
1
Order By: Relevance
“…ligandindependent) nuclear receptor. Structural studies have revealed the presence of a previously unrecognized fatty acid docked in the ligand-binding domain of HNF4α [31,32], consistent with the finding that fatty acids regulate HNF4α-dependent gene expression [52,53]. Fatty acids may also modulate STAT5 activity [54,55].…”
Section: Discussionsupporting
confidence: 72%
“…ligandindependent) nuclear receptor. Structural studies have revealed the presence of a previously unrecognized fatty acid docked in the ligand-binding domain of HNF4α [31,32], consistent with the finding that fatty acids regulate HNF4α-dependent gene expression [52,53]. Fatty acids may also modulate STAT5 activity [54,55].…”
Section: Discussionsupporting
confidence: 72%
“…G6pc gene expression was observed in an in vivo study to be modulated by polyunsaturated fatty acids [37]. Interestingly, as shown in Table 1, a transcription regulatory protein, Nr0b2, that regulates gluconeogenic genes [31], was down-regulated by metformin treatment, as observed in the case of G6pc.…”
Section: Discussionmentioning
confidence: 78%
“…We also observed that similar serial administration of metformin caused changes in similar metabolic pathways including glycolysis-gluconeogenesis and fatty acid metabolism (data not shown). Changes in the fatty acid and glycerolipid metabolism pathways may contribute to an improvement of lipid metabolism by repeated treatment with metformin, while some fatty acids might be important in modulating mRNA expression of genes such as G6pc [37]. Interestingly, changes of expression in the bile acid biosynthesis, but not the sterol biosynthesis pathway, were detected; indeed, coordinated transcriptional regulation between bile acids and gluconeogenesis [39,40], as well as suppression of gluconeogenenic genes by bile acid [31], have been reported recently.…”
Section: Discussionmentioning
confidence: 99%
“…When fish oil is substituted for saturated or polyunsaturated n-6 in the high fat diet, liver insulin resistance does not occur. N-3 LC-PUFA decrease the activity and the expression of glucose-6-phosphatase, the last enzyme responsible for liver glucose output [39,40]. Such an inhibiting effect of n-3 LC-PUFA on G6Pase activity could overcome its overactivity and help to restore normal inhibition of hepatic glucose production.…”
Section: Animal Models Of Insulin Resistancementioning
confidence: 99%